Analysis of Sb-doped ceria: Magnetism, conductivity, dielectric, specific heat and optical properties - Kolodiazhnyi, T.; Charoonsuk, T.; Spreitzer, M.; Vittayakorn, N. (My University, 2019)
We report on magnetism, charge transport, dielectric properties and specific heat of Ce1−xSbxO2 ceramics sintered at 1650 ∘C with a final antimony content of 0 ≤ x ≤ 0.0017. In contrast to other donor dopants, such as Nb, Ta, U and W, charge compensation of antimony in Ce1−xSbxO2 does not involve the formation of the Ce3+ ions as revealed by the magnetic susceptibility data. Therefore, we conclude that antimony is mainly present as Sb3+ ion and acts as an acceptor dopant in Ce1−xSbxO2. This conclusion is also supported by a very low electrical conductivity of the Sb-doped ceria that shows an activation energy Eσ ∼ 0.97 eV. This activation energy is close to that observed in oxygen conducting acceptor-doped ceria and is significantly higher than the typical Eσ ∼ 0.1–0.3 eV values reported for n-type CeO2. Below 10 K, both an anomaly in the dielectric loss and a small specific heat surplus in Sb-doped ceria indicate a low-energy dipolar relaxation probably associated with a local dynamics of the off-centered Sb3+ point defects.
Keywords: Ceria; Dielectric relaxation; Point defects; Specific heat